SOCIAL CONTROL OF MAINSTREAM MEDIA THROUGH TWITTER ACCOUNTS: SENTIMENT ANALYSIS AND SOCIAL NETWORK ON ROAD DAMAGE CASES - Anindyawardhani, Satwika Pramesti; Ardiansyah, Ardiansyah; Santoso, Edi (Jurusan Ilmu Komunkasi FISIP Universitas Jenderal Soedirman, 2024)
Abstract A video criticizing the damaged road conditions in Lampung has gone viral after being uploaded on social media. This infrastructure case has become a trending topic on the Twitter platform since April 2023. Not only in Lampung, people in other areas have also expressed their disappointment through various citizen protests. This problem prompted President Jokowi to directly review the condition of the damaged roads in Lampung and decide quickly to resolve the problem. The damaged road became a hot topic of conversation on Twitter. This research was conducted to analyze the sentiments of Twitter users towards opinions related to damaged roads and to analyze the social networks that are formed to find out the actors who play a role in spreading information. Research using descriptive and quantitative methods The process of crawling data on Twitter uses Netlytic.org and then analyzing the system level, as well as text analysis, through the keyword extractor and manual categories at Netlytic.org. The results of the study show that the main actors in the #jalanrusak communication network on Twitter are mainstream media accounts. This shows the position of the mainstream media as channeling aspirations and protecting people's rights, as well as its function as a tool of government control. Although some mainstream media also use it to spread political issues. Considering that 2023 is a political year ahead of the 2024 elections, This moment is considered strategic to attack the government and the ruling party. On the other hand, the president's quick response is seen as part of his self-image, which also has an impact on the image of the presidential candidate in his party. The sentiments of Twitter users in the discussion of #jalanrusak are more negative.